Islam's Loneliest Cosmopolitan: Badr Al-Din Hai Weiliang, the Lucknow–Cairo Connection, and the Circumscription of Islamic Transnationalism. (1st April 2018) - ,
Abstract : Badr al-Din Hai Weiliang (1912–?), a Chinese Muslim from rural Hunan, led a deeply transnational life. Hai was the only Chinese Muslim known to have studied in both India and Egypt in the modern period, spending considerable time at both the Nadwat al-'Ulama in Lucknow and al-Azhar in Cairo. After Chinese, he learned four more languages in two decades: Arabic, Urdu, English, and Persian. While the Second World War transformed him into a longtime Guomindang diplomat, his time at the Nadwa and al-Azhar in the 1930s was largely devoted to questions of Islamic unity. Hai first pursued these questions in a doctrinal mode informed by Salafi currents, then in a political mode influenced by his translation of Iqbal's "Allahabad address." His move to Cairo brought him closer to the network of al-Fath and its editor Muhibb al-Din al-Khatib, a strong voice on behalf of Islamic unity, but geopolitics soon intervened. Disillusioned by the failure of the East Turkistan Republic, Hai coped by turning toward a cultural-historical mode of imagining Islamic unity, one that did not require specific political action. The eventual result was his Arabic-language opus Relations between the Arabs and China . Overall, Hai's story defies both Sino-centric and peripheralized characterizations of Chinese Islam, showing that early-twentieth-century Chinese Islam can be used to write a highly integrated history of the Islamic world. This article contrasts Hai's numerous Arabic and Chinese writings to show how he embodied the tensions felt across the Islamic world during this period between the national and transnational community.